EVALUATION OF INTRAVARIETAL HOMOGENEITY WITHIN GRAPEVINE ROOTSTOCK CULTIVARS AS REVEALED BY SSR FINGERPRINTING - Barankova, Katerina (European Scientific Journal, ESJ, 2014)
Traditional rootstock cultivars of importance for the Mid European viticulture originate mainly from Zsigmond Teleki‘s material developed at the end of the 19-th century. Nowadays most widespread varieties derived from Teleki‘s primary vine population could be denoted SO4, Kober 5BB, Teleki 5C and Kober 125AA. Recently SSR markers became one of the most suitable and reliable tools for cultivar identification, but some problems can appear if results obtained from two independent laboratories are compared. In order to overcome this problem, the system based on reference alleles was utilised in this work. Nine rootstock genotypes from 4 varieties collected in Czech Republic were genotyped by using 9 SSR loci and compared with published genotypes from Austria, Australia, France, Italy, Hungary and USA. The major SSR profile for all rootstocks was found by comparing obtained results of different laboratories. SO4 and 125AA with almost identical SSR profile for all genotypes appears as very stable. Contrarily, the analysis of T5C and Kober 5BB revealed a higher level of heterogeneity within genotypes belonging to these cultivars.